Fasilitasi Tenaga Kesejahteraan Sosial Kecamatan pada Pemerlu Pelayanan Kesejahteraan Sosial Kategori Anak dengan Disabilitas dalam Penyelenggaraan Usaha Kesejahteraan Sosial di Kemantren Umbulharjo - Silvy Octavia S (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2022)
The District Social Welfare Personnel (TKSK) is one of the social social volunteers assigned by the Ministry of Social Affairs of the Republic of Indonesia to the success of the Social Welfare Business (UKS). TKSK has three functions, namely as coordinator, administrator, and facilitator. These functions are intended to assist those in need of Social Welfare Services (PPKS) in this case Children with Disabilities. Of course, as a facilitator, TKSK must carry out its facilitation forms to support all efforts to organize social welfare. Therefore, this study was aimed at looking at the forms of facilitation carried out by TKSK on PPKS with data collection techniques through observation, interviews, and documentation. In addition, this study uses data analysis techniques using the Miles and Huberman model (data collection, data reduction, data triangulation, data presentation, and conclusion drawing and verification). The results of this research show that the forms of facilitation carried out by TKSK as facilitators have been running optimally. It is proven that the PPKS of the Children with Disabilities group feels a significant influence with the facilitation carried out by TKSK, especially in the implementation of Social Welfare Enterprises (UKS) at Kemantren Umbulharjo so that PPKS can carry out their social functions properly and optimally